Genomics as a practical tool in sport - have we reached the starting line? - Williams, A. G.; Day, S. H.; Lockey, S. J.; Heffernan, S. M.; Erskine, R. M. (Cellular and Molecular Exercise Physiology, 2014)
The genetic component of athletic performance approximates 50%, depending on which specific element of performance is considered. Limited genetic testing is already available commercially and genetic tests are likely to become powerful tools to improve sport performance in future. Currently, however, selection of athletes for training squads or competition based on genomic data is premature. Larger volumes of longitudinal data within individual sports are needed to determine the efficacy of using genomic data in the management of elite athletes via manipulation of training load and diet based on personal genomic information.